Local Perceptions of Food Plants in Eastern Burkina Faso - Guissou, K. Marie Laure; Kristiansen, Thea; Lykke, Anne Mette (Ethnobotany Research and Applications, 2015)
<!–[if gte mso 9]> <![endif]–> Ethnobotanical interviews on the use of food plants were conducted with 90 informants from two villages in eastern Burkina Faso. A total of 25 plant species and one type of stock cube were included in a structured questionnaire regarding use, importance, reasons behind use, changes in use, and preferences, followed by a supplementary semi-structured questionnaire about reasons behind use, changes, and preferences. Most species were highly used and considered important. Adansonia digitata L., Bombax costatum Pellegr. & Vuillet, Parkia biglobosa (Jacq.) R.Br. ex G.Don, and Vitellaria paradoxa C.F.Gaertn. were particularly important and useful species. Tradition, taste, health, and the lack of other possibilities were main reasons for people using the plants. A decline in traditional food products and an emergence of new products were observed. Answers were strongly related to informants’ home-village and project-contact. There seems to be an extensive interest in health aspects and, consequently, a potential for an increased use of healthy traditional products if people are better informed about their nutritive qualities. <!–[if gte mso 9]> Normal 0 21 false false false FR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>